(untitled) (Indian Journal of Nematology, 2024)
The native isolates of entomopathogenic nematodes (EPNs) Heterorhabditis bacteriophora MK256358, H. bacteriophora MK263023, H. bacteriophora MK256378 and Steinernema cholashanense MK128155 were tested in laboratory for their virulence and reproductive potential against 4th instar larvae of Oriental armyworm, Mythimna separata Walker (Lepidoptera: Noctuidae), the serious pest of rice in Kashmir valley. All the EPN isolates were highly effective against 4th instar larvae of M. separata. Insect mortalities reached 100% within 24-48 hours at nematode concentrations of 200 infective juveniles (IJs)/larva. The trend was similar at lower concentrations of IJs, but more time was required. The best performance was shown by H. bacteriophora MK256358 and S. cholashanense MH128155 followed by H. bacteriophora MK256378 and H. bacteriophora MK263023 in terms of killing and reproductive potential. The values obtained for lethal concentration (LC50) and lethal time (LT50) of the tested EPN isolates differed significantly. Our results demonstrate the potential of the native EPN isolates against M. separata but before recommendation multi-location field trials need to be conducted to confirm their validity at farm level.